SELF EFFICACY KELUARGA TERHADAP MOTIVASI KELUARGA DALAM PEMENUHAN KEBUTUHAN DASAR SPIRITUAL PASIEN DENGAN DIABETES MELITUS DI DESA TURIREJO LAWANG - MALANG - Dwi Ana, Karisma; ., Prawito; Nuraminudin Aziz, Aditya (PRIMA WIYATA HEALTH, 2022)
Diabetes Mellitus (DM) is a metabolic disease with characteristic hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action or both. Diabetes Mellitus (DM) patients often experience problems related to changes in self-efficacy and spiritual distress or have problems with spiritual needs, such as patients not carrying out spiritual needs and patients looking desperate for the treatment process. So that Diabetes Mellitus (DM) patients need motivation from a nurse to encourage the independence of diabetes mellitus patients in fulfilling their basic spiritual needs. The purpose of this study was to determine the family's self-efficacy towards family motivation in fulfilling the basic spiritual needs of patients with diabetes mellitus in the village of Turirejo Lawang - Malang. The design of this study used a cross sectional approach. The population in this study were all families of patients with diabetes mellitus in the village of Turirejo Lawang – Malang. In this study, the sampling technique used was purposive sampling. The analysis used in this study is Spearman Rank Correlation with a value of < 0.05. The results of this study indicate that most (72%) of respondents have good family self-efficacy in meeting the basic spiritual needs of DM patients, and most (56%) of respondents have good family motivation in fulfilling the basic spiritual needs of DM patients in the village. turirejo lawang - Malang., and the results of statistical tests show that the p value = 0.00 and rs = 0.749 so it can be concluded that there is a relationship between family self-efficacy and family motivation in fulfilling the basic spiritual needs of patients with diabetes mellitus in the village of Turirejo Lawang – Malang. Self-efficacy and good motivation from the family can increase the confidence of diabetes mellitus patients in fulfilling basic spiritual needs that will shape diabetes mellitus patients. This is because nurses can increase the self-efficacy of diabetic patients by providing social support, motivation and being able to maintain a good emotional status of patients.